Hemodynamic subtype profiling in tremor-dominant and akinetic–rigid Parkinson’s disease using multi-delay pseudo-continuous arterial spin labeling imaging - Pan, Yu; Qin, Zhaoxia; Liu, Jiangbing; Wang, Wei; Zhao, Yi (Frontiers in Human Neuroscience, 2025)
PurposeThis study investigated the differences in global cerebral hemodynamics between the tremor-dominant (TD) and akinetic–rigid-dominant (ARD) subtypes of Parkinson’s disease (PD) using multi-delay pseudo-continuous arterial spin labeling (MD-pCASL) imaging and evaluated the clinical value of MD-pCASL for identifying PD subtypes.MethodsTwenty-five healthy controls (HC) and fifty-one patients with PD were enrolled: 26 in the TD group and 25 in the ARD group. Voxel-based analysis was performed to compare cerebral blood flow (CBF), arterial transit time (ATT), and cerebral blood volume (CBV) among the ARD, TD, and HC groups. Binary logistic regression analysis was used to screen independent influencing factors for predicting motor subtypes; a receiver operating characteristic curve was drawn to evaluate the diagnostic value of the multi-parameter arterial spin labeling (ASL) technique.ResultsCompared with the HC group, the ARD group exhibited increased CBF in the left thalamus, lingual gyrus, and hippocampus. Decreased CBF was observed in the left angular gyrus. The TD group exhibited decreased CBF in the left precuneus compared with that in the HC group. Compared with the TD group, the ARD group exhibited increased CBF in the left putamen, lingual gyrus, and hippocampus. Differences in CBV mirrored CBF trends. ATT prolongation was observed in the left middle temporal gyrus in the ARD group. Diagnosing ARD as positive, the following were considered potential risk factors: increased CBF in the left putamen and left lingual gyrus, increased CBV in the left lingual gyrus, and prolonged ATT in the left middle temporal gyrus. The combined areas under the curve of all indexes were 0.942; the optimal critical value was 0.766; sensitivity was 92%; and specificity was 84.6%.ConclusionBoth subtypes exhibited hypoperfusion patterns predominantly in the parieto-occipital cortex, whereas patients with ARD uniquely displayed hyperperfusion within the basal ganglia nuclei. Moreover, multi-parameter ASL showed high diagnostic efficiency in distinguishing the two subtypes. These findings highlight MD-pCASL as a valuable tool for PD subtyping and therapeutic monitoring.